(3GdOQ GdefXhe aj fVQI GdbWH GdecJhes - (3CHh YHO Gddg eMeO Hf eMeO Hf YHO GdSdGe Hf CMeO Hf YHO Gddg Lfhf GdUZjQ,J (B1326 (3g` s ((3YHjOHg eMeO s)
(3ChdgG (B:s
(3CeG HYO , aEfc CjgG GdCN dUGOb CQSdJ JSCd YeG ThT Hg GdHYV Ydi ENhGffG GdJLGfjjf , ef Cf TQW GdEfJaGY HGdTjN chfg MjkG s
(3BNQgG (B:s
(3hdjcf gPG BNQ eG CQOfG EjQGOg aj gPG GdLhGH hcGf GdaQGZ VMhg jhe GdEKfjf GdNGeS hGdYTQjf SfI (B1318 (3hcJHg YHjOQHg eMeO cfhf hGdMeO ddgQH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B445 - (3U(B480s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B77s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B168 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(644 (3c(B) s
Keywords: (3GdJGQjNs